Forest ecosystem genomics and adaptation: EVOLTREE conference report - Kremer, A.; Vinceti, B.; Alia, R.; Burczyk, J.; Cavers, S.; Degen, B.; Finkeldey, R.; Fluch, S.; Gomory, D.; Gugerli, F.; Koelewijn, H.P.; Koskela, Jaarko; et al. (Springer, 2011)
This article is a summary report of the international conference "Forest ecosystem genomics and adaptation" organized by the EVOLTREE Network of Excellence in San Lorenzo de El Escorial (Madrid), Spain, from 9 to 11 June 2010. Main achievements and results of the network are presented for the eight thematic sessions and a stakeholder session. The conference has shown that adaptive responses of trees to biotic or abiotic selection pressures can now be investigated at the gene level for traits of adaptive significance. Candidate genes have been catalogued for phenological and drought-related traits in important tree families (Salicaceae, Fagaceaea and Pinaceae), and their variation in natural populations is being explored. Genomics can now be integrated in ecological research to investigate evolutionary response to climate changes in a wide range of species. New avenues of research were also highlighted as the exploration of gene networks involved in adaptive responses and the combination of experimental and modelling approaches to disentangle components of evolutionary changes triggered by climate change. The main focus of the conference was the adaptation of trees to environmental changes. The conference was organized in eight thematic sessions ranging from genomic approaches aiming at identifying genes of adaptive significance to practical issues regarding mitigation options for combating climate change. A dialogue between scientists and end users took place in the form of an ad hoc stakeholder session. A panel of end users from various forest and policy-making institutions expressed their expectations, and the discussions with the scientists addressed the potential applications of research findings to the management of genetic resources in the context of climate changes. The conference was introduced by two keynote speakers Dr. Pierre Mathy from the European Commission, Directorate General of Research, and Dr. Allen Solomon, former National Program Leader for Global Change, US Forest Service. All the thematic sessions were introduced by high-level invited speakers from the respective fields.